On the development of SCILAB compatible software for the analysis and control of repetitive processes - Hładowski, Łukasz; Cichy, Błażej; Gałkowski, Krzysztof; Rogers, Eric (Zielona Góra: Uniwersytet Zielonogórski)
Łukasz Hładowski, Błażej Cichy, Krzysztof Gałkowski, Eric Rogers In this paper further results on the development of a SCILAB compatible software package for the analysis and control of repetitive processes is described. The core of the package consists of a simulation tool which enables the user to inspect the response of a given example to an input, design a control law for stability and/or performance, and also simulate the response of a controlled process to a specified reference signal.
Keywords: repetitive processes; simulation; SCILAB